Net-Zero Emission Industry: Efficiency of EU Regulation in the Context of American Approach - Grzegorczyk, Filip; Kozera, Łukasz (International Journal of Energy Economics and Policy, 2025)
The relevance of the study is due to the aggravation of the global climate crisis, which requires urgent and coordinated action by the leading participants in international relations. The European Union and the United States play a key role in the global economy and have a significant impact on industrial emissions. Given their role, a comparison of their legal approaches to achieving zero emissions is crucial for the development of an effective global policy in this area. The purpose of the article is to identify the optimal legal mechanisms and strategies for the implementation of zero-emission industry. The article provides a detailed analysis of the legal regulation of industrial emissions in the EU and the US. The authors examine the monitoring and reporting mechanisms, the role of case law, and the specifics of economic incentives in both jurisdictions. The article identifies the advantages of a centralized regulatory system in the EU compared to a flexible but fragmented approach in the US. The authors reveal the key challenges of harmonization, including different levels of economic development and regulatory heterogeneity. The author also substantiates legal proposals for improving zero-emissions regulation, including the unification of standards and strengthening international cooperation. The scientific novelty of the paper lies in the development of generalized recommendations that take into account the most successful practices of both regions and offer a model for combining rigorous supranational coordination with market instruments.